Least Mean Error Algorithm for Determining the Radome Dimension of Planar Antenna - Adya Pramudita; Yuyu Wahyu (Universitas Ahmad Dahlan, 2016)
Antennas are generally contructed from metallic materials; therefore it is prone to corrosion when installed outdoors. Radome is an important part of an outdoor antenna that serves to protect the antenna from environmental conditions. Radome structure is not expected to have a significant influence on the characteristics of the antenna. Parametric study is generaly applied in finding the optimum antenna dimenssion included radome. A method for guiding a parametric study proses in finding the optimum antenna dimensions has investigated and proposed in this paper. In this study, a method for determining the optimum radome dimension for planar antenna by applying the algorithm Least Mean Error (LME) has investigated. LME algorithm is used to find the optimum dimensions of the radome. The simulation results show that the proposed method can be applied to determine the dimensions of a planar antenna.